2006
DOI: 10.1051/0004-6361:20065111
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the nature of INTEGRAL objects through optical spectroscopy

Abstract: We present further results from our onging optical spectrophotometric campaign at the Astronomical Observatory of Bologna in Loiano (Italy) on unidentified hard X-ray sources detected by INTEGRAL. We observed spectroscopically the putative optical counterparts of the INTEGRAL sources IGR J00234+6141, IGR J01583+6713, IGR J06074+2205, IGR J13091+1137 and IGR J20286+2544. We find that the first two are Galactic objects, namely a Cataclysmic Variable at a distance d ∼ 300 pc and a Be/X transient High-Mass X-ray B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 56 publications
4
77
1
Order By: Relevance
“…IGR J08408-4503 was discovered in the Vela region on 2006 May 15 with INTEGRAL during a short flare lasting less than 1000 s . Its optical counterpart was later identified as the supergiant star HD 74194 located at 3 kpc, thus confirming that this source belongs to the SFXT class Masetti et al, 2006a). IGR J08408-4503 was observed in outburst several times with INTEGRAL and Swift Leyder et al, 2007;Sidoli et al, 2009c;Barthelmy et al, 2009).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…IGR J08408-4503 was discovered in the Vela region on 2006 May 15 with INTEGRAL during a short flare lasting less than 1000 s . Its optical counterpart was later identified as the supergiant star HD 74194 located at 3 kpc, thus confirming that this source belongs to the SFXT class Masetti et al, 2006a). IGR J08408-4503 was observed in outburst several times with INTEGRAL and Swift Leyder et al, 2007;Sidoli et al, 2009c;Barthelmy et al, 2009).…”
Section: Discussionmentioning
confidence: 72%
“…A number of studies were dedicated to the search of the optical counterpart of this source (Halpern and Tyagi, 2005;Tomsick et al, 2006b;Masetti et al, 2006a;Reig and Zezas, 2009;Reig et al, 2010). Finally Reig et al (2010) identified it with a relatively bright (V = 12.3) B0.5Ve star located at a distance of ∼ 4.5 kpc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations